Criminalization of Corporate Business Policy as a Corruption Crime: Study of ASDP Case Ira Puspadewi (Decision No. 68/Pid.Sus-TPK/2025/PN Jkt.Pst) - Pongkor, Dionysius Yasmin (Journal of Law, Politic and Humanities, 2026)
This study analyzes the criminalization of corporate business policy in the corruption case involving Ira Puspadewi, President Director of PT ASDP Indonesia Ferry, as adjudicated in Decision No. 68/Pid.Sus-TPK/2025/PN Jkt.Pst. Employing a normative juridical method with conceptual and case approaches, the research examines the tension between formal legal certainty and substantive justice in the application of Articles 2 and 3 of the Indonesian Anti-Corruption Law. The findings reveal that the court predominantly relied on a formalistic interpretation emphasizing the fulfillment of statutory elements, particularly unlawful conduct and state financial loss, despite the absence of proven mens rea or personal enrichment. The dissenting opinion invoked the Business Judgment Rule, highlighting the necessity of distinguishing managerial risk from criminal misconduct. The study concludes that excessive formalism risks overcriminalizing corporate discretion and underscores the need for a proportional, context-sensitive enforcement paradigm.